Translocal style communities : Hip-hop youth as cultural theorists of style, language and globalization - Samy Alim, H. (Pragmatics, 2009)
This article addresses issues that lie at the intersection of debates about language, Hip Hop Culture, and globalization. Critically synthesizing a wide range of recent work on Hip Hop and foregrounding issues of youth agency as evidenced by Hip Hop youths metalinguistic theorizing, the article presents an empirical account of youth as cultural theorists. Hip Hop youth are both participants and theorists of their participation in the many translocal style communities that constitute the Global Hip Hop Nation. Highlighting youth agency, the article demonstrates that youth are engaging in the agentive act of theorizing the changes in the contemporary world as they attempt to locate themselves at the intersection of the local and the global. The article concludes by calling for a linguistic anthropology of globalization characterized by ethnographic explorations of and a theoretical focus on popular culture, music, and mass-mediated language as central to an anthropological understanding of linguistic processes in a global era.
Keywords: création; hip hop cultures; jeunesse; linguistique